Neural correlates of semantic ambiguity resolution in paucisymptomatic bipolar disorder patients. (30th October 2021) - Raucher‐Chéné, Delphine; Obert, Alexandre; Gierski, Fabien; Benzerouk, Farid; Terrien, Sarah; Barrière, Sarah; Portefaix, Christophe; Besche‐Richard, Chrystel; Kaladjian, Arthur
Highlights: Bipolar patients present thought disorders underpinned by semantic impairments. Semantic inhibition was explored through a semantic ambiguity resolution task. Bipolar patients displayed altered fronto-temporo-parietal activations. These semantic-related activations could reflect compensative mechanisms. Abstract: In addition to symptoms specifically related to mood dysregulation, patients with bipolar disorder (BD) show frequent alterations in formal thought organization. A disruption in semantic processing, notably in semantic inhibition, is one of the possible mechanisms that might explain this modified organization. However, to date, little is known about these mechanisms and their underlying neural substrates. This study aimed to identify the neural correlates of the semantic inhibition process in BD patients in comparison to healthy controls. Seventeen BD patients and 17 matched controls were recruited and underwent a 3T MRI scan. A semantic ambiguity resolution task was used during the scan to explore semantic inhibition. Whole-brain analyses were conducted on 13 BD patients and 16 controls. When compared to controls, BD patients had stronger activation in the bilateral temporal areas and right middle frontal gyrus, and less activation in the right hippocampus, parahippocampal area, and bilateral precunei. The present study revealed an altered fronto-temporo-parietal semantic inhibition network in BD patients that could reflect compensative mechanisms or modified semantic processing inducing abnormal thought organization, which has a major impact on the occupational and social functioning of the BD population.